17‐2: A method of improving image contrast based on Dual Cell display. Issue 1 (25th September 2020) - Zhao, Yizhuo; He, Tao; Chen, Yinhong; Zhou, Mingzhong
Abstract : Based on the Dual cell structure display, this paper proposes an effective contrast enhancement scheme. By using the lower cell to control the backlight brightness, local dimming is realized at the pixel level. Combined with spatial filtering, the ghosting problem of the Dual cell structure display is solved.